Modelling the Development of Child Prisoners Based on Justice - Wilsa, Wilsa; Rahmat, Diding; Mahmud, Izmi Izdiharuddin B Che Jamaludin (Universitas Negeri Gorontalo, 2024)
This study examines the importance of reconstructing the development model for child prisoners through justice-based diversion, focusing on how to better accommodate their right to quality education, as guaranteed by international resolutions, conventions, and Indonesia's 1945 Constitution. The research highlights the need for appropriate educational models that enable child prisoners to reintegrate into society as responsible, law-abiding citizens. Using a normative juridical approach, the study explores literature-based sources to propose a model incorporating formal and non-formal education to enhance the self-competence of child prisoners. The proposed educational model aims to equip children with skills and knowledge, ensuring they can reintegrate successfully into their families and communities after serving their sentences. By aligning educational approaches with the principles of justice, the model offers a pathway to reducing recidivism and improving the long-term prospects for child prisoners. The study emphasises the need for a comprehensive and child-centred development program that reflects the child's best interests and supports their rehabilitation.